Paediatric CT scan usage and referrals of children to computed tomography in Germany-a cross-sectional survey of medical practice and awareness of radiation related health risks among physicians - Merzenich Hiltrud; Krille Lucian; Hammer Gael; Kaiser Melanie; Yamashita Shunichi; Zeeb Hajo (BMC, 2012)
Abstract Background Computed tomography (CT) is a major source of ionizing radiation exposure in medical diagnostic. Compared to adults, children are supposed to be more susceptible to health risks related to radiation. The purpose of a cross-sectional survey among office-based physicians in Germany was the assessment of medical practice in paediatric CT referrals and to investigate physicians' knowledge of radiation doses and potential health risks of radiation exposure from CT in children. Methods A standardized questionnaire was distributed to all paediatricians and surgeons in two defined study areas. Furthermore, the study population included a random sample of general practitioners in the two areas. The questionnaire covered the frequency of referrals for paediatric CT examinations, the medical diagnoses leading to paediatric CT referrals, physicians' knowledge of radiation doses and potential health risks of radiation exposure from CT in children. Results A total of 295 (36.4%) physicians responded. 59% of the doctors had not referred a child to CT in the past year, and approximately 30% referred only 1-5 children annually. The most frequent indications for a CT examination in children were trauma or a suspected cancer. 42% of the referrals were related to minor diagnoses or unspecific symptoms. The participants underestimated the radiation exposure due to CT and they overestimated the radiation exposure due to conventional X-ray examinations. Conclusions In Germany, the frequency of referrals of children to computed tomography is moderate. The knowledge on the risks from radiation exposure among office-based physicians in our sample varied, but there was a tendency to underestimate potential CT risks. Advanced radiological training might lead to considerable amendments in terms of knowledge and practice of CT referral.